PENGARUH KININ, METABOLIT KININ DAN KLOROKUIN TERHADAP HEMOLISIS DARAH PENDERITA MALARIA DAN DARAH MANUSIA SEHAT SECARA IN VITRO - Kumolosasi, Endang
Abstract: The influence of quinine, quinine metabolites and chlo roquin at concentrations of 10-9M-10-2M at 0%-0.9% NaCl tonicity on hemolysis of blood from malaria patients and healthy people had been investigated in vitro. The degree of hemolysis of blood from healthy people and apparently also from malaria patients did not differ significantly (P<0.05) at a concentration of 10-9 M, at blood level concentration (5.10-5M for quinine and 3.10-7M for chloroquin) and at concentration of 10-3M at all tonicities studied, but the degree of hemolysis was significantly greater for chloroquin relative to quinine at a concentration of 10-6M and tonicity of 0.25%, 0.55%, and 0.90% NaCl (P<0.05). The degree of hemolysis was very different for the two compounds at a concentration of 10-2M and tonicities of 0.25%-0.90% NaCl (P<0.01); quinine increased while chloroquin decreased hemolysis. The same profile was seen with blood from malaria patients. The degree of hemolysis of blood from healthypeoplecaused by quinine and quinine metabolites at a concentration of 10-9M, at blood level (5.10-5M) and at 10-3M, at 0.55% NaCl tonicity did not differ significantly (P<0.05). This probably applied also to blood from malaria patients. The degree of hemolysis by quinine metabolite at concentration of 10-6M and 0.55% NaCl tonicity, was significantly higher relative to quinine (P<0.05) and at concentration of 10-2M the reverse was observed (P<0.01). At a concentration of 10-2m and 0.55% NaCl tonicity quinine as well as its metabolites apparently caused a higher degree of hemolysis in blood from malaria patients than in blood from healthy people.